2023
DOI: 10.18805/bkap590
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Correlation of Technology Know-how of Farm Entrepreneurs of Samastipur District of Bihar, India

Abstract: Background: In the process of agricultural development, the prime mover is considered to be the new farming technology. Technology plays a pivotal role in every aspect of the agricultural phenomenon. It enhances productivity and transparency at every step of agricultural movements. Quality and quantity are managed through this facility which improves farmers’ socioeconomic status and mental health. From this perspective, technological involvement must be necessary with the human values. Methods: The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Another important variable is the education of women in terms of number of schooling years, which has positive significant impact on the adoption of technology with t-value of 5.42. Education level of household heads and training participation significantly affected farmers' adoption decision (Dilebo, 2017;Kumari, 2023). Most studies found that better-educated farmers, regardless of gender, are more likely to adopt new technologies but women farmers with less education, less land access are less likely to adopt new technologies (Quisumbing, 1995).…”
Section: Educationmentioning
confidence: 99%
“…Another important variable is the education of women in terms of number of schooling years, which has positive significant impact on the adoption of technology with t-value of 5.42. Education level of household heads and training participation significantly affected farmers' adoption decision (Dilebo, 2017;Kumari, 2023). Most studies found that better-educated farmers, regardless of gender, are more likely to adopt new technologies but women farmers with less education, less land access are less likely to adopt new technologies (Quisumbing, 1995).…”
Section: Educationmentioning
confidence: 99%